THE MEASURING OF THE GINI, THEIL AND ATKINSON INDICES FOR GEORGIA REPUBLIC AND SOME OTHER COUNTRIES (Globalization and Business, 2018)
When studying the economic structure of society qualitative and quantitative methods are closely related to each other. In particular when analyzing the economic structure of society inequality indicessuch as the (generalized)Gini index, the Hoover index, the first and second Theil indices, the first and second Atkinson indicesand other are used. In this article, we investigate the relationship between these indices and in some cases prove that they can be calculated by different formulas. In addition these indices will be calculated for the following countries: Azerbaijan,Armenia, China, Estonia, France, Georgia, Germany, Greece,Iran, Israel, Italy, Japan, Latvia, Lithuania, Moldova, Russia,Turkey, Ukraine, United States.